Prevalence of pain and treatment outcomes among cancer patients in a Malaysian palliative care unit - Mejin M; Keowmani T; Abdul Rahman S; Liew J; Lai J; Chua M; Che Wan I (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Pain remains one of the most common and debilitating symptoms of advanced cancer. To date, there is a lack of studies on pain and its treatment among Malaysian palliative care patients. Objective: This study aimed to explore the prevalence of pain and its treatment outcomes among adult cancer patients admitted to a palliative care unit in Sabah, Malaysia. Methods: Of 327 patients screened (01/09/15-31/12/17), 151 patients with assessed self-reported pain scores based on the numerical rating scale of 0-10 (current, worst and least pain within the past 24 hours) upon admission (baseline), 24, 48 and 72 hours post-admission and discharge were included. Pain severity and pain score reductions were analysed among those who experienced pain upon admission or in the past 24 hours. Treatment adequacy was measured by the Pain Management Index (PMI) among discharged patients. The PMI was constructed upon worst scores categorised as 0 (no pain), 1 (1-4, mild pain), 2 (5-6, moderate pain), or 3 (7-10, severe pain) which is then subtracted from the most potent level of prescribed analgesic drug scored as 0 (no analgesia), 1 (non-opioid), 2 (weak opioid) or 3 (strong opioid). PMI≥0 indicated adequate treatment. Results: Upon admission, 61.1% [95%CI 0.54:0.69] of 151 patients presented with pain. Of 123 patients who experienced pain upon admission or in the past 24 hours, 82.1% had moderate to severe worst pain. Throughout patients' ward stay until discharge, there was an increased prescribing of analgesics and adjuvants compared to baseline, excluding weak opioids, with strong opioids as the mainstay treatment. For all pain score types (current, worst and least pain within the past 24 hours), means decreased at each time point (24, 48 and 72 hours post-admission and discharge) from baseline, with a significant decrease at 24 hours post-admission (p<0.001). Upon discharge (n=100), treatment adequacy significantly improved (PMI≥0 100% versus 68% upon admission, p<0.001). Conclusions: Accounting for pain's dynamic nature, there was a high prevalence of pain among cancer patients in the palliative care unit. Continuous efforts incorporating comprehensive pain assessments, evidence-based treatments and patient education are necessary to provide adequate pain relief and end-of-life comfort care.